Study of flexural strength on concrete bundled bars beams. Issue 2 (March 2021) - Walujodjati, E; Tjondro, J A; Permana, S; Johari, G J
Abstract: Reinforced concrete beams as structural elements that are often found are elements that are quite large in their role in bearing loads. Judging from the function of support as a bearer of tensile force, it is possible if the reinforced concrete beams are made with different numbers and areas of reinforcement. Reinforcement bundles are used if there is a cross-sectional dimension limitation without the distance between the reinforcement conditions being met. Beams with 2 reinforcement bundles are made to see the flexural capacity obtained. With the dimensions of the beam 150 mm x 200 mm x 1050 mm, a bundle of 2 reinforcement with a diameter of 10 mm is mounted on the tensile section of reinforced concrete beams. With a four-point bending test, a nominal bending moment is obtained. Single-section square cross-section analysis with cross-sectional area obtained using the equivalent diameter of the reinforcement bundle compared to the flexural test results. The bending moment capacity between experiment and analysis obtained the appropriate results. The bending capacity value of the two reinforcement bundles is still large so that the bending failure has not been reached.